The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/bpo.0000000000001973
|View full text |Cite
|
Sign up to set email alerts
|

Clubfoot Activity and Recurrence Exercise Study (CARES)

Abstract: Background: Approximately half of treated clubfoot patients initially corrected with the Ponseti method experience relapse that requires additional treatment. The consequences of relapse on childhood activity levels have not been well studied. Ponseti noted lower functional ratings at 18-year follow-up in clubfoot patients who had undergone tibialis anterior tendon transfer for relapse. Methods: Clubfoot Activity and Recurrence Exercise study (CARES) is an observational, prospective cohort study that compares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A prospective, observational cohort study evaluated physical activity in patients who had clubfoot, were <10 years of age, and did or did not have relapse and found no difference in daily step counts, step intensity, or distance walked. Step counts in all patients with clubfoot were similar to general population metrics 53 .…”
Section: Footmentioning
confidence: 53%
“…A prospective, observational cohort study evaluated physical activity in patients who had clubfoot, were <10 years of age, and did or did not have relapse and found no difference in daily step counts, step intensity, or distance walked. Step counts in all patients with clubfoot were similar to general population metrics 53 .…”
Section: Footmentioning
confidence: 53%
“…Aulie et al3 found that 96% of school aged children treated for idiopathic clubfoot with the Ponseti method have normal function when compared with age-matched controls in the same population. Several other studies similarly demonstrated comparable activity levels and have similar patient reported outcome scores when compared with the general pediatric population 4–6. For patients diagnosed in utero, Mahan et al7 found that prenatal counseling of families by an orthopaedic surgeon did not decrease parental anxiety; however, anxiety decreased as treatment progressed.…”
Section: Resultsmentioning
confidence: 91%
“…Several other studies similarly demonstrated comparable activity levels and have similar patient reported outcome scores when compared with the general pediatric population. [4][5][6] For patients diagnosed in utero, Mahan et al 7 found that prenatal counseling of families by an orthopaedic surgeon did not decrease parental anxiety; however, anxiety decreased as treatment progressed.…”
Section: Clubfootmentioning
confidence: 99%
“…Relapse patients show multiple structural impairments which contribute to gait issues at the ankle and knee 24,25. Recent studies show lower clinical status in relapse patients compared with nonrelapse patients,26 but after relapse treatment, comparable physical activity was found 27. In the current clubfoot group, 34% of the parents reported additional surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Recent studies show lower clinical status in relapse patients compared with nonrelapse patients, 26 but after relapse treatment, comparable physical activity was found. 27 In the current clubfoot group, 34% of the parents reported additional surgical interventions. However, because of the diversity of terminology used to describe interventions, we decided not to use this information to further analyze the data in respect to possible relapse.…”
Section: Median (Iqr) Median (Iqr) Pmentioning
confidence: 93%